2003
DOI: 10.1111/j.1348-0421.2003.tb02801.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the F Gene of Contemporary Mumps Virus Strains Isolated in Japan

Abstract: Mumps virus (MuV) strains isolated in Saitama Prefecture, Japan, from 1997 to 2001, were examined by analyzing the SH and the F gene nucleotide sequences. The results of the SH gene analysis showed that only genotype G was found in 2001 as well as in 2000, and that genotype J, which we proposed as a new genotype in a previous study, was from a different lineage than the genotype J described by Tecle et al. (J. Gen. Virol. 82, 2675–2680). We therefore, propose to rename the genotype as K to avoid confusion. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…These results revealed that the amino acid sequence of the mumps F protein was the most conserved gene of the MuV; this is because of the critical function of this protein that makes it an intolerable mutation site for viral survival. Other reports with similar conclusions have recently been published [Kashiwagi et al, 1999;Tecle et al, 2000;Uchida et al, 2003].…”
Section: Sequence Analysis Of the F Genesupporting
confidence: 67%
See 2 more Smart Citations
“…These results revealed that the amino acid sequence of the mumps F protein was the most conserved gene of the MuV; this is because of the critical function of this protein that makes it an intolerable mutation site for viral survival. Other reports with similar conclusions have recently been published [Kashiwagi et al, 1999;Tecle et al, 2000;Uchida et al, 2003].…”
Section: Sequence Analysis Of the F Genesupporting
confidence: 67%
“…Variation in the signal sequence (amino acids 1-19) and transmembrane region (amino acids 487-507) of F protein was observed as previously reported [Tecle et al, 2000;Uchida et al, 2003;Ivancic et al, 2004]. Despite the high degree of divergence in predicted amino acid sequences of the signal peptide and transmembrane regions among different strains, the other predicted structural and functional motifs of fusion protein of MuV were remarkably similar.…”
Section: Sequence Analysis Of the F Genesupporting
confidence: 64%
See 1 more Smart Citation
“…The SH-PCR product covers the entire length of the SH gene, known to be the most variable region of the mumps genome. The F gene, the target of the real-time PCR, appears to be the most conserved (Uchida et al, 2003). While mumps virus is considered genetically relatively stable, a PCR targeting the most conserved region is less likely to loose sensitivity due to strain variation.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype G has been identified for the first time by Jin et al [2000]. Since then mumps virus isolates belonging to this genotype appeared in United Kingdom [Jin et al, 2000[Jin et al, , 2004 and Japan [Uchida et al, 2001[Uchida et al, , 2003Inou et al, 2004]. A closer inspection on the relationship with mumps virus isolates submitted to the GenBank revealed extremely high similarity with wild-type mumps virus strains originated in United Kingdom in the period 1997-2002: Wrek1/UK97 (99%), Dud1-2/UK98, Kent4/UK97, UK02-304, UK00-47x4, UK0046x7, UK00322x2 and UK99-162x3 (98% for all) (Fig.…”
Section: Sequence Analysis Of the Sh Genementioning
confidence: 97%